Sati tradition its origin and change as reflected in Around the World in 80 Days: A sociological approach - Zakiyyah Attasyriky; Hendra Darmawan (Universitas Ahmad Dahlan)
This research aims at investigating the main character's disobedience toward Sati tradition in Around the World in 80 Days: a Sociological Approach. The research method used in this research is a descriptive qualitative method so the researcher analyzes the data in this research through description. There are two main results of this research. First, the main character’s disobedience toward Sati tradition are (1) the main character’s disobedience in India Forest (being displeased with government authority, hope of reform); (2) the main character’s disobedience in Calcutta (law enforcement); (3) the main character’s disobedience in United States of America (injustice occur). Second, the moral values can be taken from the novel are divided into positive and negative values.